DIAGNOSTICS AERODYNAMIC OF AIRCRAFT IN THE PROCESS OF EXPLOITATION - Казак, В.; Шевчук, Д. (Science-based technologies, 2011)
The mathematical model of authentication of sudden damages of the outside of the airplane is offered, which al-lows at the known descriptions and problem spaces in the process of flying exploitation to define probability of stay the airplane. It is offered the block diagramme of the automated monitoring and diagnostic system of an aerodynamic condition of the airplane while in service and reorganisation control to them in special situations